2021
DOI: 10.1111/1462-2920.15637
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of dimethylsulfide‐degrading methanogens and sulfate‐reducing bacteria in anoxic sediments along the Medway Estuary, UK

Abstract: Methane is a powerful greenhouse gas but the microbial diversity mediating methylotrophic methanogenesis is not well-characterized. One overlooked route to methane is via the degradation of dimethylsulfide (DMS), an abundant organosulfur compound in the environment. Methanogens and sulfate-reducing bacteria (SRB) can degrade DMS in anoxic sediments depending on sulfate availability. However, we know little about the underlying microbial community and how sulfate availability affects DMS degradation in anoxic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 96 publications
(130 reference statements)
0
8
0
Order By: Relevance
“…Methanolobus are known DMS degraders with several strains isolated from an oil well, marine, lake and estuarine sediments 10,11 . We also recently showed Methanolobus to be the dominant DMS-degrading methanogen genus in brackish sediments from the Medway Estuary, UK 8 . Furthermore, a psychrotolerant Methanolobus strain has been isolated from a saline lake sediment in Siberia, indicating that this genus has members that can grow in low temperatures, as were measured in Baltic Sea sediments 56 .…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Methanolobus are known DMS degraders with several strains isolated from an oil well, marine, lake and estuarine sediments 10,11 . We also recently showed Methanolobus to be the dominant DMS-degrading methanogen genus in brackish sediments from the Medway Estuary, UK 8 . Furthermore, a psychrotolerant Methanolobus strain has been isolated from a saline lake sediment in Siberia, indicating that this genus has members that can grow in low temperatures, as were measured in Baltic Sea sediments 56 .…”
Section: Discussionmentioning
confidence: 71%
“…Intriguingly, the sulfate concentrations in the sediments below 9 cm from all three sites increased significantly compared to the initial concentrations (Supplementary Figure 3). This suggests that hydrogen sulfide produced as one of the end products of DMS degradation was converted to sulfate, which led to cryptic sulfur cycling in these incubations 8 .…”
Section: Sediment Depth Profiles Of Dms Methane and Co2mentioning
confidence: 98%
See 1 more Smart Citation
“…In anoxic sediments, DMS can be degraded to potent greenhouse gases methane and carbon dioxide (CO 2 ) by methylotrophic methanogens, further highlighting the significance of DMS [ 8 ]. Cultivation-based studies on DMS-dependent methanogenesis showed that this process is carried out by certain methanogens of the genera Methanomethylovorans , Methanolobus , Methanosarcina and Methanohalophilus [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased sulfate availability caused by, for example, intrusion of sulfate-laden seawater to estuarine wetlands ( 10 ), will likely enable SRB to produce more H 2 S, utilizing H 2 and/or organic acids such as acetate and lactate as electron donors. The competition from SRB for H 2 and acetate may reduce methane production by hydrogenotrophic and acetoclastic methanogens ( 7 , 11 ). Characterization of these microbial interactions will provide insights into community metabolism under changing environmental conditions and allow modeling of metabolic flux rates among community members.…”
Section: Introductionmentioning
confidence: 99%